Climate Change Refugees: Striving for an Established Definition for Broader and Better Management - Kusumo, Ayub Torry Satriyo; Adiastuti, Anugerah (UI Scholars Hub, 2024)
According to the Inter-governmental Panel for Climate Change (IPCC) 2021, The increase in global warming has accelerated the pace at which glaciers melt, thereby leading to a mass migration of people. The United Nations High Commissioner for Refugees (UNHCR) reported that approximately 21.5 million people migrated to more decent places due to climate or geographical conditions. This category of people are often called climate refugees and when the apply for international refugee status, it is declined due to the inability to meet the established criteria outlined by the International Refugees Convention. Unfortunately, the phenomena associated with climate refugee have not been reviewed carefully through legal instruments. The process has also been worsened by legal proposals, multilaterally, and the international community. Therefore, this research proposed that climate change refugees are not international refugees. Specific and specialized bodies are needed to resolve the issue associated with this category of immigrants because of the magnitude of the problem worldwide.